A Cross-Sectional Evaluation of Medical Students, Interns and Postgraduates Regard for Patients with Substance Abuse using the Medical Condition Regard Scale (MCRS) in Andhra Pradesh - Mediboina, Anjali; Bhupathi, Meghana; Rachakonda, Sai Teja; Islam, Rojah (International Journal of Medical Students, 2025)
BACKGROUND: Positive attitudes and empathy from healthcare providers are essential in the effective treatment of patients with substance abuse, impacting both treatment outcomes and patient well-being. In India, attitudes towards substance abuse often reflect a lack of awareness and limited understanding of effective rehabilitation procedures. The Medical Condition Regard Scale (MCRS) is a valuable tool and has been shown to effectively capture the complexity of provider attitudes. However, its use in the Indian context for substance abuse has been limited. AIMS: The study aims to evaluate and compare the regard for patients with substance abuse among medical students, interns, and postgraduates using the MCRS, and to determine any potential significant differences in attitudes based on gender, age, and occupation. METHODS: A cross-sectional survey was conducted between June and August 2024 using an online self-administered questionnaire distributed via Google Forms through social media. The survey included medical students (MBBS 3rd and 4th year), interns, and postgraduates in Andhra Pradesh. The questionnaire collected informed consent and demographic information (gender, age, state, year of study, marital status, and religion), and responses to the MCRS, which includes eleven items rated on a six-point Likert scale (1 = strongly disagree, 6 = strongly agree), with five items reverse-scored. The total regard score was derived from the sum of individual item scores, ranging from 11 to 66. Statistical analyses were performed using Microsoft Excel and RStudio v4.3.3. Chi-square tests were used to compare the number of participants with positive (total score 44 and above) and negative (total score 43 and below) regard against demographic variables. RESULTS: A total of 206 responses were collected, of which 187 met the inclusion criteria. The majority of participants were male (n=98, 52.4%), aged 21-25 years (n=133, 71.1%), interns (n=85, 45.5%), unmarried (n=179, 95.7%), and Hindu (n=160, 85.6%). The median total regard score was 44, with a mean score of 44.7 (SD=6.7), reflecting a generally positive regard for patients with substance abuse. The highest positive regard was noted for the statement, "I wouldn’t mind getting up on call nights to care for patients with substance-use disorder" (mean=4.4, SD=1.1), indicating a position of uncertainty leaning towards agreement. The highest negative regard was for the reverse-scored statement, "Treating patients with substance-use disorder is a waste of money" (mean=4.8, SD=1.2), indicating disagreement with this viewpoint. Chi-square analysis showed that females had a significantly higher positive regard compared to males (p=0.04085). No significant differences were found with respect to age groups (p=0.3442) or occupation (p=0.6534). CONCLUSION: This study highlights a generally positive regard toward patients with substance abuse. However, limitations include respondent bias, and restriction to a single state, potentially limiting generalizability. The skewed distribution of respondents, with a predominance of unmarried and Hindu participants, prevented analysis of associations with religion and marital status. Future research should therefore include diverse regions and demographic groups. Targeted educational interventions for healthcare professionals, and incorporating substance abuse care into medical curricula and providing opportunities for hands-on experience can help to reduce stigma and improve patient outcomes.